Transcriptome analysis of Phytophthora cactorum infecting strawberry identified RXLR effectors that induce cell death when transiently expressed in Nicotiana benthamiana - Ghimire, Bikal; Gogoi, Anupam; Poudel, Mandeep; Stensvand, Arne; Brurberg, May Bente (Frontiers in Plant Science, 2024)
Phytophthora cactorum is a plant pathogenic oomycete that causes crown rot in strawberry leading to significant economic losses every year. To invade the host, P. cactorum secretes an arsenal of effectors that can manipulate host physiology and impair its defense system promoting infection. A transcriptome analysis was conducted on a susceptible wild strawberry genotype (Fragaria vesca) 48 hours post inoculation with P. cactorum to identify effectors expressed during the early infection stage. The analysis revealed 4,668 P. cactorum genes expressed during infection of F. vesca. A total of 539 secreted proteins encoded by transcripts were identified, including 120 carbohydrate-active enzymes, 40 RXLRs, 23 proteolytic enzymes, nine elicitins, seven cysteine rich proteins, seven necrosis inducing proteins and 216 hypothetical proteins with unknown function. Twenty of the 40 RXLR effector candidates were transiently expressed in Nicotiana benthamiana using agroinfiltration and five previously unreported RXLR effector genes (Pc741, Pc8318, Pc10890, Pc20813, and Pc22290) triggered cell death when transiently expressed. The identified cell death inducing RXLR effectors showed 31–66% identity to known RXLR effectors in different Phytophthora species having roles in pathogenicity including both activation and suppression of defense response in the host. Furthermore, homology analysis revealed that these cell death inducing RXLR effectors were highly conserved (82 - 100% identity) across 23 different strains of P. cactorum originating from apple or strawberry.